2019
DOI: 10.1001/jamanetworkopen.2019.18561
|View full text |Cite
|
Sign up to set email alerts
|

Association of Use of Online Symptom Checkers With Patients’ Plans for Seeking Care

Abstract: Author Contributions: Drs Winn and Crotty had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 5 publications
1
55
1
1
Order By: Relevance
“…It remains to be seen how many patients would actually follow advice on where to go next, but in the survey of US Isabel symptom checker users, about half (14/26, 54%) of those advised to go to the emergency department reported that they did so [ 29 ]. Another recent paper reported broadly similar findings from over 150,000 encounters with the Buoy Health symptom checker: 18.8% of patients who had planned to visit primary care reduced the urgency of care they would seek, and 2.6% increased the urgency of their intended level of care [ 30 ]. The differences in findings between the studies are not large, and likely primarily reflect the major design difference between the studies: our study explored those patients who have already chosen to attend the primary care practice, whereas the Buoy study explored intentions expressed at home.…”
Section: Discussionmentioning
confidence: 82%
“…It remains to be seen how many patients would actually follow advice on where to go next, but in the survey of US Isabel symptom checker users, about half (14/26, 54%) of those advised to go to the emergency department reported that they did so [ 29 ]. Another recent paper reported broadly similar findings from over 150,000 encounters with the Buoy Health symptom checker: 18.8% of patients who had planned to visit primary care reduced the urgency of care they would seek, and 2.6% increased the urgency of their intended level of care [ 30 ]. The differences in findings between the studies are not large, and likely primarily reflect the major design difference between the studies: our study explored those patients who have already chosen to attend the primary care practice, whereas the Buoy study explored intentions expressed at home.…”
Section: Discussionmentioning
confidence: 82%
“…A limitation of this study was that a systematic and comprehensive selection process was not used to select the symptom assessment apps to be included. The non-systematic selection criteria used were that, at the time of selection: (i) Babylon and Ada are leading symptom assessment smartphone apps in the UK; (ii) K Health, WebMD and Ada are the most used in US (usage data from Sensely, https://www.sensely.com); (iii) Mediktor and Buoy have existing published data [7,27]; and, (iv) Your.MD has a similar user experience and user interface to Babylon and Ada and has been compared with them in small non-peer reviewed studies [21,23].…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…through diagnostic-decision support). While it has been argued that the accuracy of urgency advice may be the most important output from a health assessment app, the condition suggestions may be valuable to support patient decision making [27]. To address the effect of patients entering data directly into an app about their own acute conditions, an observational investigation is currently underway in an acute clinical setting in the US by investigators including co-authors of this study.…”
Section: Unanswered Questions and Future Researchmentioning
confidence: 99%
“…Commercial products using artificial intelligence to capture patient's symptoms and health concerns from emails to guide scheduling, and online tools that use chatbots to triage patient requests for appointments are already under development. 21,22 The interpretation of this study's results has limitations. First, we used email as a proxy for patient engagement, which might not be an appropriate assumption.…”
mentioning
confidence: 85%